The History of Political Thought as secular genealogy: the case of liberty in early modern England. Issue 1 (2nd January 2017) - Condren, Conal
ABSTRACT: The History of Political Thought originated in, and partially remains an adjunct to the academic study of politics. As such it is not a mere subject matter or authentic tradition of speculation, but a secularising genealogy in some tension with an impulse to rigorous historicity. It provides an under-acknowledged context for the thinkers and concepts placed within it. The difficulties and consequent distortions are illustrated with reference to seventeenth-century discussions of liberty. It is argued that notions of negative liberty and Republican liberty as an ideological alternative are secularising genealogical projections that distort the character of seventeenth-century debate; but that republican liberty can be reformulated in more historically plausible terms as a special case of one of the entailments of contentious office-holding in and beyond a secularised conception of the political. Thomas Hobbes's conceptions of liberty provide a concluding illustration.